The analysis of integration process of Ukraine into the European Union - Koschiyenko, M. V.; Karlyuk, S. V. (Харківський національний університет ім. В. Н. Каразіна, 2019)
Positive and negative consequences of the introduction of Ukraine into the European Union on economic, political, and social levels are analyzed in the article. SWOT-analysis on the issue has been performed.
Keywords: competitiveness; European choice; European standards